Analisis Pengelolaan Persediaan Dan Perputaran Piutang Terhadap Tingkat Profitabilitas Koperasi Pada KPN Nur Afiah Unit Usaha Toko RSUP Wahidin Sudirohusodo Makassar Periode (2020-2022) - Rizky Ridayani; Pra Gemini; Fausiah Fausiah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
The aim of this research is to determine the relationship between Inventory Turnover and Receivables Turnover on Cooperative Profitability Levels. The research method used in this research is the comparative analysis method. The sample used in this research used a purposive sampling method, namely financial reports in the form of balance sheets and profits/losses of KPN Nur Afiah RSUP Wahidin Sudirohusodo Makassar for the period 2020-2022. Net Profit Margin (NPM) is an analysis in this research to show that Inventory Turnover and Receivables Turnover on Profitability Levels have a very big influence. Furthermore, Inventory Turnover describes how much current assets turn into cash, likewise, Receivables Turnover describes how much current assets turn into cash. Meanwhile, profitability describes how big a cooperative or company's ability is to generate profits.